2008
DOI: 10.1016/j.appet.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Food demand functions in mice

Abstract: Male mice (mus musculus) of a mixed B6/129 background were used to establish food demand functions in a closed economy. The mice lived continuously in operant chambers and worked for 20-mg nutritionally complete food pellets. First, a series of incrementing fixed ratio (FR) costs per pellet were imposed, and the results showed that demand declined as unit price increased. The number of meals taken per day was dependent on the temporal criterion used to define a meal, but the number of meals did not change acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…From another perspective, designs that facilitate or ensure a strict correspondence between rewards earned and consumed might be preferable for some studies. Our work is consistent with published observations showing that a strict correspondence can be achieved with higher-order FR scheduling [45]. Moreover, training mice on FR3 or FR5 schedules of reinforcement may be useful for studies culminating in PR testing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From another perspective, designs that facilitate or ensure a strict correspondence between rewards earned and consumed might be preferable for some studies. Our work is consistent with published observations showing that a strict correspondence can be achieved with higher-order FR scheduling [45]. Moreover, training mice on FR3 or FR5 schedules of reinforcement may be useful for studies culminating in PR testing.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we next evaluated operant responding and reward consumption using FR3 and FR5 schedules of reinforcement, reasoning that by increasing the unit cost of each reward [45], we might improve the correspondence between rewards earned and consumed. On Days 1 and 2 of testing, male C57BL/6J mice (n=36) were acclimated to operant testing during 60-min sessions using an FR1 schedule of reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…Given the apparent and procedural differences among these human studies, we developed a protocol to investigate whether mice can adjust their total daily intake to different experimentally-imposed meal frequencies. Our previous studies in mice have found substantial individual variation in meal parameters (Chaney & Rowland 2008); many mice seem to take some prolonged but slow meals, or apparent grazing, especially at night. One purpose of the present experiments is to examine the adaptation of mice to what amounts to an imposed meal pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we have reported closed-economy food demand functions for mice under a variety of conditions in which they emit behavioral responses to obtain food pellets (Atalayer & Rowland 2009; Chaney & Rowland 2008). In those studies, we have found that when work is imposed as an inescapable fixed unit price (FUP), total food intake declines at relatively high unit prices (eg 50-100 responses per 20 mg pellet), but that the meal pattern remains relatively constant despite the fact that inter-pellet intervals and meals become extended in time as FUP increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation